2017
DOI: 10.1016/j.idcr.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous rectus sheath hematomas in dengue hemorrhagic fever: A case report

Abstract: Muscle hematomas are rare complications in dengue hemorrhagic fever (DHF). We report a case of 58-year-old-female admitted with dengue fever who developed spontaneous rectus sheath hematoma complicating DHF. She presented with progressive thrombocytopenia with platelet count reaching 13000/μL at its lowest point. There was evidence of plasma leakage and persistent cough during the course of illness. During the recovery phase, she reported severe abdominal pain and developed hematoma in the right rectus sheath,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…SRSHs may be confused mostly with appendicitis, renal colic and abdominal hernia that can cause pain in the right lower abdominal quadrant as well as with gynecological diseases and other intra-abdominal pathologies such as diverticulitis, biliary diseases, pancreatitis, intestinal obstruction, colorectal diseases, abdominal tumors, and ruptured aortic aneurysm [1]. Although USG is used for initial examination due to easy access, fast application, and absence of radiation, contrast-enhanced CT is preferred as a primary diagnostic modality with 100% sensitivity and specificity in establishing a diagnosis, and it can even show active bleeding [14, 15]. CT also prevents unnecessary surgical interventions by excluding other intra-abdominal pathologies, provides information on the origin, extension, and nature of the hematoma, and helps in identification of the treatment option by classifying rectus sheath hematomas by their anatomic structures, sizes, and localizations.…”
Section: Discussionmentioning
confidence: 99%
“…SRSHs may be confused mostly with appendicitis, renal colic and abdominal hernia that can cause pain in the right lower abdominal quadrant as well as with gynecological diseases and other intra-abdominal pathologies such as diverticulitis, biliary diseases, pancreatitis, intestinal obstruction, colorectal diseases, abdominal tumors, and ruptured aortic aneurysm [1]. Although USG is used for initial examination due to easy access, fast application, and absence of radiation, contrast-enhanced CT is preferred as a primary diagnostic modality with 100% sensitivity and specificity in establishing a diagnosis, and it can even show active bleeding [14, 15]. CT also prevents unnecessary surgical interventions by excluding other intra-abdominal pathologies, provides information on the origin, extension, and nature of the hematoma, and helps in identification of the treatment option by classifying rectus sheath hematomas by their anatomic structures, sizes, and localizations.…”
Section: Discussionmentioning
confidence: 99%
“…Supplemental Table S5 summarizes the other less common surgical manifestations in dengue. 16,23,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] Seven studies and several case reports/series were found mainly from Asian countries. A total of 296 patients were described.…”
Section: Common Causes Of Acute Abdomen In Dengue Infectionsmentioning
confidence: 99%
“…[5][6][7] Among bleeding complications, muscles hematomas are rare and the common sites of intramuscular hematomas are rectus sheath, psoas and iliacus muscles. 8…”
Section: Discussionmentioning
confidence: 99%